Integrating Fintech and Technological Innovation to Strengthen Digital Entrepreneurship and Reduce Unemployment in Cilacap - Indra Rachmawati; Nursanti Dwi Yogawati; Annisa Rahayu Pangesti; Syarifah Aini (Universitas Medan Area, 2025)
This study examines how technological innovation and financial technology support job creation in the MSME sector of Cilacap Regency, with digital entrepreneurship serving as a mediating variable. The re-search addresses the ongoing gap between strong MSME growth and limited employment absorption at both the national and regional levels. Using a mixed-methods approach, the study combines survey-based quantitative analysis using Structural Equation Modeling with qualitative insights from interviews that clarify technology adoption patterns, barriers to fintech use, and challenges in digital literacy. The find-ings indicate that innovation and fintech adoption positively affect job creation directly and through digital entrepreneurship, demonstrating the value of digital transformation for small business growth. However, these gains are constrained by unequal access to digital tools, limited technological readiness, and persistent literacy gaps among MSME actors. The study underscores the need for targeted digital em-powerment efforts, expanded access to technology, and stronger capacity-building programs to enhance MSME competitiveness. Strengthening digital skills and improving fintech utilization can support broa-der employment opportunities and contribute to regional economic resilience. These measures are essential for ensuring that digital transformation produces inclusive benefits, enables sustainable MSME development, and strengthens the overall capacity of local enterprises to generate stable employment in the region.